Determination of storage area and hub via the enhanced elevator kinematics optimization method - Walailak Atthirawong; Pongchanun Luangpaiboon (Journal of Industrial and Production Engineering, 2021)
Locations of storage area and hub are important factor of transport cost. To determine locations, increased transport cost against variable numbers of storage areas and hubs must be considered at the same time. This research shows how to manage locations, via the zero-one integer programming model, which considers total transport costs as incurred by every activity in the transport process. An Enhanced Elevator Kinematics Optimization method was developed from the Aungkulanon, Luangpaiboon, and Montemanni’s Elevator Kinematics Optimization algorithm to determine the optimal locations of storage areas and hubs. It was concluded that the company should have one storage area located in Samut Prakan Province and 12 hubs around the country, compared to the existing 11 hubs, which would result in 3.1% cost reduction. Also, from a further study on storage area fixed cost reduction, it would be possible to increase storage area size leading to a 4.1% cost reduction.
Keywords: Urban and Freight Transport Logistics; Elevator Systems and Control; Urban Transport Systems Analysis